How is motor learning affected by stroke? - Mokhtari, P.; Sheikh, M. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Introduction Cerebrovascular accidents impose a devastating effect on the lives of their victims. These involve sensori-motor, cognitive, psychological as well as numerous psychosocial disturbances. On the other hand, many daily and lifelong motor skills are learned through a series of complex mechanisms in the nervous system (motor learning) which might also be affected during the process of an ischemic stroke. Although the most prominent disorder caused by stroke (i.e., paralysis) has been investigated thoroughly throughout past decades, there are few studies focusing on other aspects of stroke pathology including motor learning. This study was carried out to delineate the consequences of a cerebrovascular accident on the process of motor learning. Methods Forty subjects who had suffered from an ischemic anterior circulation cerebrovascular accident (20 with left- and 20 with right-sided lesion) were enrolled as the experimental group. The mean interval between the stroke attack and the study was about 2 years. Forty right-handed control subjects, with matched sex, age and handedness were also registered. Both group practiced a fast spatial-temporal task in either augmented (100%) or faded (67%) feedback circumstances. The subjects of both groups were evaluated for acquisition, recall and re-acquisition after 198 trials. Results Both groups showed significant improvement in performance accuracy and consistency over the acquisition phase and there was no significant difference in the performance patterns of the subjects during the acquisition, recall and reacquisition phases. Besides, there was no significant difference between the two feedback exposure programs, except in the acquisition period (P<0.05). According to the interaction of the subjects with the feedback conditions, significant difference was not observed between the subject and control groups. Discussion/ Conclusions These results suggest that an anterior circulation stroke affects the motor control and performance processes, but it does not deteriorate the process of learning motor skills.